Cardinal orientation and melting temperature effects for PCM-enhanced light-walls in different climates. (November 2019) - Fateh, Amirreza; Borelli, Davide; Weinläder, Helmut; Devia, Francesco
Highlights: Thermal analysis of behaviour of PCM insulation layer, using a validated model. PCMs thermal non linearity is taken into account using the hysteresis model. A set of PCM melting temperatures, thicknesses, and positions inside the wall have been evaluated. The thermal performance was evaluated for four wall cardinal orientations in two different sites. The effects of the parameters is discussed for two different summertime climates. Abstract: The use of Phase Change Materials (PCMs) in buildings, aimed at peak shavings and energy savings, has a long history and many applications. In the last decade, the use of PCMs embedded in thermal insulation layers for building envelopes become an interesting option for lightweight structures. Nevertheless, the possibility of profitably exploiting the thermal properties of PCMs is strongly affected by the harmonised combination of the parameters that determine the thermal consumption of the building. In order to analyse the effects of a PCM insulation layer in detail, this paper presents a complete dynamic model of a typical lightweight wall, containing a layer of PCMs, using a thermal model which also considers the hysteresis of specific heats. Five different cases were evaluated to study the effect of PCM positioning on energy utilisation in two different climates (Würzburg, Germany and Denver, USA), considering the effect of solar radiation on differently oriented walls, in summer. Results confirmed that the strong non-linearity of the PCMs' behaviour and of the weather boundary condition deeply affect the thermal performance of the building, being the main reason for this effect an increase of the thermal capacity of the PCM layer and the external temperature.